An ethnographie study of students’ oral performance in the mixed francophone- anglophone university classroom - Tomlinson, Timothy (Canadian Journal of Higher Education, 1989)
Mixedfrancophone-anglophone classes have become an important, yet controversial feature of post-secondary education in Canada. However, arguments concerning the suitability (or lack thereof) of these classes have not been based on empirical research documenting what actually occurs in them. This paper describes an ethnographic case study which begins to address this need. The study examines the relationship between students’ use of French and English in five mixed classes at a bilingual university and their access to subject-matter knowledge and social networks. Initial analyses reveal that language brokerage is an important process in two of the classes observed. In order to illustrate how this process works, an excerpt of classroom interaction is presented. The broader implications of language brokers are then discussed, with reference to recent work on mixed classes in Franco-Ontarian elementary and secondary schools. The paper concludes with suggestions for future research and a consideration of some policy implications of mixed classes.